Narrative of Deficit and Authentic Portrayals of Mental Illness and Cultural Sensitivities in Young Adult Literature - Elsie Lindy Olan; Kia Jane Richmond (University of Oklahoma Libraries, 2023)
This article sheds light on the narrative of deficit that often surrounds characters who have mental illness in young adult literary novels (YAL) and critiques the manner in which that narrative perpetuates the stigma of mental illnesses such as depression, anxiety, post-traumatic stress disorder, and/or obsessive-compulsive disorder. We focus on two 21st century young adult novels whose characters are accurately depicted as having mental illness and whose authors authentically share the characters' successes and struggles as well as the impact of their mental illness symptoms on family, friends, and neighbors. Our aim is to analyze and critique these novels to inform researchers and authors of YAL about the danger of romanticizing stigma surrounding mental illness, which, through the descriptions of characters' behaviors and language used by the authors (whether intentional or not), can perpetuate the narrative of deficit that is associated with characters with mental illness.